If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 9 = 6x Reorder the terms: 9 + y = 6x Solving 9 + y = 6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + y = -9 + 6x Combine like terms: 9 + -9 = 0 0 + y = -9 + 6x y = -9 + 6x Simplifying y = -9 + 6x
| 3x^2-132+12=0 | | x-8/7=7/3 | | (x+4)+(x-3)+x=19 | | b+12.4=19.8 | | 7/a-8=8/2 | | 5x+3(2x-4)=43 | | 3v^2-2v-4=0 | | 2.5y+5= | | 9y-8y+3y= | | 18-(2x+8)=14 | | n-3n=13-4n | | -4y=-4x+10 | | n+5/7=2/3 | | 3x=y+11 | | 3.5+10m=7.98 | | 7r^2+6r+1=0 | | x+7/7=8/4 | | 16-9g=70 | | y=4-38-1.3 | | X+-z=yforz | | 3.5y+8= | | -4+x=3x+8 | | 2y=x-5 | | r^2-9r-12=0 | | -86-12=14a | | 5x-15+6=5x-9 | | 6.5x+3= | | -8x+5=37 | | 8(x+7)+5=8x+7 | | -10v=-5 | | k^2+9=38 | | -4d+6=16-9d |